2018
DOI: 10.1242/bio.031427
|View full text |Cite
|
Sign up to set email alerts
|

pH controls spermatozoa motility in the Pacific oyster (Crassostrea gigas)

Abstract: Investigating the roles of chemical factors stimulating and inhibiting sperm motility is required to understand the mechanisms of spermatozoa movement. In this study, we described the composition of the seminal fluid (osmotic pressure, pH, and ions) and investigated the roles of these factors and salinity in initiating spermatozoa movement in the Pacific oyster.The acidic pH of the gonad (5.82 ± 0.22) maintained sperm in the quiescent stage and initiation of flagellar movement was triggered by a sudden increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 40 publications
5
29
0
Order By: Relevance
“…Spermatozoa motility in Pacific oysters is a key factor for reproduction and notably depends on concentrations of ions including K + , Ca 2+ and Na + (Alavi et al, 2014). Indeed, the percentage of motile sperm is drastically reduced in Na + -free seawater (Boulais et al, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Spermatozoa motility in Pacific oysters is a key factor for reproduction and notably depends on concentrations of ions including K + , Ca 2+ and Na + (Alavi et al, 2014). Indeed, the percentage of motile sperm is drastically reduced in Na + -free seawater (Boulais et al, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…VSL of sea urchin spermatozoa was shown to be 170-240 µm sec -1 in Hemicentrotus pulcherrimus (Hiramoto and Baba 1978) and 150-200 µm sec -1 in Paracentrotus lividus (Fabbrocini and D'Adamo 2017). The factors contributing to the relatively low velocity observed for black-lip pearl oyster in our study may be twofold: firstly, the activation of oyster sperm motility and its duration is associated with internal concentration of cAMP (Demoy-Schneider et al 2014) under internal pH control (Boulais et al 2018). Maximum sperm velocity may not have been reached in our assay conditions, although only 4 min separated the transfer to the swimming solution and the first video records.…”
Section: Discussionmentioning
confidence: 52%
“…Actually, Li et al (2010b) observed alterations of enzyme activity involved in metabolism of C. carpio frozen/thawed spermatozoa. Butts et al (2011) reported a decrease in anti-trypsin activity in Atlantic cod frozen/thawed spermatozoa and Zilli et al (2004) observed an increase of malate dehydrogenase activity in sea bass Dicentrarchus labrax frozen/thawed spermatozoa, but did not observe change in activity of β-aspartate aminotransferase, isocitrate dehydrogenase or β-D glucuronidase. This decrease in enzyme activity, combined with lower mitochondrial respiration could explain why the ATP content is lower in frozen/thawed blacklip pearl oyster spermatozoa, as these metabolic processes could be limiting for an efficient cellular ATP supply (Cosson, 2012) in fish spermatozoa.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies on the mollusc sperm biological characteristics, cryopreservation and quality assessment have become more numerous since reviewed by Gwo (Gwo, ; Hassan, Qin, & Li, ). These studies concerned oyster species (Boulais et al, ; Suquet et al, ; Suquet, Rimond, et al, ), pearl oyster species (Demoy‐Schneider, Levêque, Schmitt, Le Pennec, & Cosson, ; Demoy‐Schneider, Schmitt, Le Pennec, Suquet, & Cosson, ; Zheng et al, ) and so on. However, studies for scallop species were limited to Pecten maximus (Suquet, Arsenault‐Pernet, Ratiskol, & Mingant, ; Suquet, Gourtay, et al, ; Suquet, Malo, et al, ; Suquet, Quéré, et al, ), Argopecten purpuratus (Lamarck, 1819) (Dupré, Covarrubias, Goldstein, Guerrero, & Rojas, ; Espinoza, Valdivia, & Dupre, ), Chlamys farreri (Li, Li & Xue, 2000; Xue, ) and Patinopecten yessoensis (Yang et al, ; Yang, Yang, Liu, & Zhou, , ).…”
Section: Introductionmentioning
confidence: 99%